Microprocessor-based monitoring and analysis system for physiological parameters in bioengineering - Toe Myint. (2008)
This report described the development of microprocessor-based or computerised monitoring and analysis for appropriate physiological parameters, such as ECG, the electrocardiograph signals. ECG was chosen as the most appropriate parameter based on current and urgent requirements of inter-disciplinary collaboration works with cardiologists and cardiac surgeons at the Singapore General Hospital.